Cognitive Behavior Therapy (CBT) Plus Remembrance Intervention in Diabetes Mellitus Patients - Fatmawati, Fatmawati; Nurlina (Jurnal ABDIMAS Panrita, 2024)
The incidence of DM continues to increase substantially worldwide. The epidemic of diabetes mellitus and its ever-increasing complications is a global health threat. It is estimated by 2035 by the International Diabetes Federation that 592 million (1 in 10 people) worldwide will develop DM (90% of type 2 DM and Asia is the epicenter of the current Type 2 DM epidemic (Zheng et al., 2018) One form of nonpharmacological treatment in patients with depression. One form of nonpharmacological treatment in patients with depression is cognitive behavioral therapy (CBT) intervention. Cognitive behavioral therapy is seen to be very effective in the treatment of depression. The method used in this service is cognitive behavioral therapy combined with remembrance therapy on glycemic control, simultaneous influence of cognitive behavioral therapy combined with remembrance therapy on depression control and glycemic control of sufferers The training activity will be held in September 2023, attended by 30 DM patients in the Bontobangun Health Center work area. The purpose of the implementation of this service is to improve the quality of life of DM sufferers in handling depression experienced Keywords : cognitive behavioral therapy, DM